SPIRITUALISASI HUMAN BEING DALAM PENDIDIKAN ISLAM - Septiana Purwaningrum (Edudeena : Journal of Islamic Religious Education, 2019)
Abstract: The dichotomy of science really has a role in bringing the dualism of education. The impact of the dualism in education is that general education institutions deepen in mastering modern science and lack of religious values. On the other hand, the religion education deepens the religious knowledge and lags behind the development of modern science. The demarcation separation between general education and religious education makes the stratification between two educations eventually, in which the position of islamic education is onsidered lower. The dichotomy of science must be stopped immediately so this community does not continue to fall into deterioration. The solution to overcome the dichotomy of science can be done through the Islamization of science and the spiritualization of human being. This article is written qualitatively based on library research by using primary source and some relevant secondary sources. Through descriptive-analytical methods, the writer tries to elaborate the material related to the dichotomy of science, the islamization of science and the spiritualization of human beings in Islamic Education to realize non-dichotomic Islamic education. Abstrak: Dikotomi ilmu sangat berperan dalam memunculkan dualisme pendidikan. Dampak dari dualisme pendidikan adalah lembaga pendidikan umum lebih memperdalam penguasaan ilmu pengetahuan modern dan kering akan nilai-nilai agama. Di sisi lain, pendidikan agama lebih memperdalam pengetahuan agama dan tertinggal dari perkembangan ilmu pengetahuan modern. Pemisahan secara demarkatis antara pendidikan umum dan pendidikan agama pada akhirnya melahirkan stratifikasi antar dua pendidikan tersebut, di mana posisi pendidikan Islam dianggap lebih rendah. Dikotomi ilmu dalam pendidikan Islam harus segera dihentikan agar umat ini tidak terus menerus terjerembab dalam keterpurukan. Solusi untuk mengatasi dikotomi ilmu dapat dilakukan melalui islamisasi sains dan spiritualisasi human being. Artikel ini ditulis secara kualitatif berbasis library research dengan menggunakan sumber primer dan beberapa sumber sekunder yang relevan. Melalui metode deskriptif-analitis, penulis berupayauntuk mengelaborasi materi terkait dikotomi ilmu, islamisasi sains, dan spiritualisasi human being dalam Pendidikan Islam untuk mewujudkan pendidikan Islam yang nondikotomik.